Aerobic exercise combined with chlorogenic acid exerts neuroprotective effects and reverses cognitive decline in Alzheimer’s disease model mice (APP/PS1) via the SIRT1/ /PGC-1α/PPARγ signaling pathway - Shi, Dan; Hao, Zikang; Qi, Wenxiao; Jiang, Fengyi; Liu, Kerui; Shi, Xiao (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s disease (AD) is a prevalent neurodegenerative disease account for 60–80% of the total number of people with dementia, but its treatment and prevention strategies are still in a long process of exploration. It has been reported that a healthy lifestyle may be an effective non-pharmacological intervention for the prevention and treatment of AD, including increased physical activity and the consumption of polyphenol-rich foods. This study, therefore, investigated the effects of 8 weeks of moderate-intensity aerobic exercise (EX), administration of chlorogenic acid administration (GCA), and a combination of both (EX+GCA) on β-amyloid (Aβ) deposition, inflammatory factors, oxidative stress markers, neuronal damage, and cognitive performance in the brains of AD model mice (APP/PS1) and which signaling pathways may be responsible for these effects. The study used Western blot to detect the expression of signaling pathway-related proteins, enzyme-linked immunosorbent assay to detect the expression of inflammatory factors, hematoxylin–eosin staining to detect hippocampal neuronal morphology, immunohistochemistry to detect changes in Aβ deposition in the hippocampus, an oxidative stress marker kit to detect oxidative stress status and the Morris water maze to detect changes in cognitive performance. This study showed that an 8-week intervention (EX/GCA/EX+GCA) activating the SIRT1/PGC-1α signaling pathway improved oxidative stress, neuroinflammation, Aβ deposition, and cognitive performance in mice. However, there was no obvious difference between the EX and GCA groups. In contrast, the combined EX+GCA intervention was significantly better than phase EX or GCA. Our study suggests that although relief of Aβ deposition, neuroinflammation, oxidative stress, neuronal damage, and cognitive decline could also be achieved with EX or GCA, the combined EX+GCA intervention showed better results. These relief effects on AD-related conditions may be obtained by mediating the activation of the SIRT1/PGC-1α signaling pathway. This study is the first to explore the improvement of AD-related conditions with a combined lifestyle of EX+GCA. This healthy lifestyle could be a candidate option for the treatment of AD.